Textbook Evaluation as a Means of Discovering Learners' and Teachers' Needs - Svetlana Bogolepova (National Research University Higher School of Economics, 2016)
Needs analysis is considered an essential step which normally precedes English for Academic Purposes course design. It allows course developers to identify the tasks the target audience has to complete, and the skills they need to master. Based on the experience of the 'English for Academics' textbook writing project, the paper shows that needs analysis can be extended to the materials evaluation stage of textbook development. The piloting undertaken at this stage involved a questionnaire which required qualitative and quantitative responses from teacher and learner participants. The respondents were encouraged to evaluate different aspects of the course implementation, e.g. timing, relevance, difficulty, sequence, clarity of instructions, etc., and suggest improvements. The questionnaire was analysed which provided course developers with the opportunity to identify additional learners' needs and to explore teachers' needs and expectations, which in many respects coincided with each other. Consequently, the learning and teaching materials were restructured in accordance with the evaluation. The changes which were introduced into the textbook and the Teachers' Notes are described. It is concluded that piloting can be an instrument to expose both pedagogical and linguistic needs, thus, providing for the triangulation of the methods and reliability of the results.